Relación de autoeficacia, apoyo social y percepción de amenaza en la adherencia al tratamiento de la DM2. Comparación entre pacientes de consulta externa y GAM - Sánchez Arellano, Anastacia Alhelí (Universidad Michoacana de San Nicolás de Hidalgo, 2018)
The problem of lack of adherence to treatment in patients with DM2 leads to the need to identify whether self-efficacy, social support and the risk perception are related to compliance with medical recommendations. In addition, in the mutual help groups (GAM) only biological markers have been evaluated to know if this strategy impacts on the adherence to the treatment of DM2 leaving out the psychological variables. Objectives: Analyze the relationship between self-efficacy, social support, the risk perception with adherence to treatment and determine if there are differences in social support, self-efficacy, the risk perception of and adherence to treatment among adults with DM2 who attend only the outpatient consultation and those who attend the GAM. Method: correlational transectional design with a non-probabilistic sample for convenience, with 166 DM2 participants attending medical attention at the health secretary and the ISSSTE of Michoacán. The Self-Efficacy Instrument for Diabetes Treatment, the Social Support Instrument in Diabetes, the sub-scale of perceived severity and the sub-scale of perceived susceptibility of the ECS-DM2 / PG and the Adherence to Treatment Scale Diabetes Mellitus II, version III, were applied. Results: Self-efficacy and social support correlated positively with adherence to treatment. Patients who attended GAM showed statistically significant differences in self-efficacy and Hemoglobin Glucosylated (HbA1c). Discussion and conclusion: adherence to treatment in patients with DM2 implies a series of behaviors, which are related to self-efficacy and social support. These variables do not seem to be sufficient for patients to follow all the medical recommendations indicated in DM2.

La problemática de la falta de adherencia al tratamiento en pacientes con DM2, lleva a la necesidad de identificar si la autoeficacia, el apoyo social y la percepción de amenaza se relacionan con el cumplimiento de las recomendaciones médicas. A su vez en los grupos de ayuda mutua (GAM) sólo se han evaluado marcadores biológicos, para saber sí esta estrategia impacta en la adherencia al tratamiento de la DM2 dejando fuera las variables psicológicas. Objetivos: Analizar la relación que existe entre la autoeficacia, el apoyo social, la percepción de amenaza con la adherencia al tratamiento y determinar si existen diferencias en el apoyo social, la autoeficacia, percepción de amenaza y adherencia al tratamiento entre los adultos con DM2 que acuden sólo a Consulta Externa y los que acuden al GAM. Método: diseño transeccional correlacional con un muestreo no probabilístico por conveniencia, con 166 participantes que acuden a atención médica en la Secretaria de Salud y del ISSSTE de Michoacán. Se aplicaron el Instrumento de Autoeficacia al Tratamiento en Diabetes, el Instrumento de Apoyo Social en la Diabetes, la sub-escala de severidad percibida y la sub-escala de susceptibilidad percibida de la ECS-DM2/PG y la Escala de adherencia al tratamiento de la Diabetes Mellitus II, versión III. Resultados: La autoeficacia y el apoyo social correlacionaron positiva y significativamente con la adherencia al tratamiento. Los pacientes que acuden al GAM mostraron diferencias estadísticamente significativas en la autoeficacia y la Hemoglobina Glucosilada (HbA1c). Discusión y conclusión: la adherencia al tratamiento en los pacientes con DM2 implica una serie de conductas, que se relacionan con la autoeficacia y el apoyo social. Estas variables parecen no ser suficientes para que los pacientes sigan todas las recomendaciones médicas indicadas en la DM2.
Facultad de Psicología. Maestría en Psicología
Keywords: info:eu-repo/classification/cti/4; FP-M-2018-0095; Tratamiento; Apoyo social; Percepción de amenaza; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3584